Peran Roh Kudus dalam Mewujudkan Ecclesia Domestica dan Mencegah Oikia Meristhe di Jemaat GMIM Imanuel Toraget - Mumu, Andre Shevcenco; Poluan, Agnes Relly (AISTHETIKOS Jurnal Ilmu Teologi dan Seni, 2026)
The Christian family is theologically understood as the Ecclesia Domestica (house church), an ideal "covenant community." However, in the pastoral reality at the GMIM Imanuel Toraget congregation, some families fail to achieve this ideal and fall into the condition of Oikia Meristhe (a divided household), a phenomenon proven to have no direct correlation with socio-economic status. This research analyzes this phenomenon from a Pneumatological theology perspective, using a descriptive qualitative method and library research with a biblical and systematic theology approach. The analysis indicates that the theological root of Oikia Meristhe is not external factors, but rather the unsubdued "ego" and "idolatry of the heart," which are manifestations of the "works of the flesh" (sarx). Conversely, the Ecclesia Domestica is actualized through participation in the nature of Christ (the Second Person of the Trinity), facilitated by the means of grace. This study concludes that the Holy Spirit (the Third Person of the Trinity) is the determinant divine Agent in this dynamic. The Holy Spirit actively works to prevent Oikia Meristhe by applying the death of Christ to "put to death" the ego (mortification of the sarx), and simultaneously actualizes the Ecclesia Domestica by applying the resurrection life of Christ, which produces the "Fruit of the Spirit" and empowers spiritual disciplines (such as family worship). Family wholeness in Toraget, therefore, is not a sociological or economic achievement, but a supernatural work of the Holy Spirit within a Trinitarian framework.